1998
DOI: 10.1002/(sici)1096-9861(19980222)391:4<470::aid-cne5>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and cortical afferents to the dorsal lateral geniculate nucleus of the turtle,Emys orbicularis: A combined axonal tracing, glutamate, and GABA immunocytochemical electron microscopic study

Abstract: The dorsal lateral geniculate nucleus (GLd) of the turtle Emys orbicularis has been analyzed with axonal tracing methods and immunocytochemical techniques for glutamate (GLU) and gamma-aminobutyric acid (GABA), in combination with a quantitative study of the morphologic characteristics, distribution, and synaptology of the retinofugal and corticofugal terminals. Ultrastructural observations show that the vast majority of retinal terminals (Rtr) have clear, rounded synaptic vesicles and account for 16% of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 94 publications
(153 reference statements)
4
16
0
Order By: Relevance
“…Tracing studies have shown that a proportion (about 37%) of the SR terminals represents the corticogeniculate projection, and immunocytochemical studies have shown that all the Rtr and a large proportion of SR, including cortical terminals, are highly glutamate‐ir. Comparing our findings with those obtained by others (see references in Kenigfest et al, 1995, 1998) in birds and mammals reveals many important similarities in the fine structure of the GLd, particularly with respect to the cytological properties of retinal and cortical terminals, their targets, and their immunochemical properties.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Tracing studies have shown that a proportion (about 37%) of the SR terminals represents the corticogeniculate projection, and immunocytochemical studies have shown that all the Rtr and a large proportion of SR, including cortical terminals, are highly glutamate‐ir. Comparing our findings with those obtained by others (see references in Kenigfest et al, 1995, 1998) in birds and mammals reveals many important similarities in the fine structure of the GLd, particularly with respect to the cytological properties of retinal and cortical terminals, their targets, and their immunochemical properties.…”
supporting
confidence: 86%
“…Large arrows indicate thick and thin smooth fibers, small arrows indicate thin varicose fibers labeled in the cell plate (GLdc), in the inner (GLdin) and outer (GLdon) neuropil of the nucleus, and in the optic tract (TrO) either after pretectal (Kenigfest et al, 2000) or tectal (Belekhova et al, 2003) tracer injection. Gray areas represent unlabeled cell bodies of glutamatergic projection neurons in the cell plate, and open areas represent unlabeled cell bodies of GABAergic local neurons in the inner and outer neuropil and optic tract (Kenigfest et al, 1995, 1998). D and L, respectively, represent the dorsal and lateral axes of the brain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the reptilian thalamus, which is mostly devoid of descending projections from the cortex, interneurons have only been identified in the retinorecipient regions (Rio et al, 1992; Pritz and Stritzel, 1994; Kenigfest et al, 1995, 1998; Butler, 2008). In birds however, where reciprocal connections between the thalamus and the cortex are more abundant, thalamic interneurons are distributed more widely (Granda and Crossland, 1989; Veenman and Reiner, 1994; Butler, 2008).…”
Section: Introductionmentioning
confidence: 99%